Probiotic and cyanide degrading potentials of pediococcus pentosaceus and pichia exigua isolated from cassava products effluent - Banwo, K.; Ojetunde, J.T.; Falade, T. (Informa UK Limited, 2023)
Cassava tubers contain high levels of cyanogenic glucosides that are toxic when consumed. Lactic acid bacteria and yeast from the effluent generated during the processing of cassava products were assessed for cyanide degradation and probiotic potentials. Pediococcus sp. OG08 and Pichia sp. OG4 had higher bile salt tolerance (p < 0.05) in 0.3 % bile salts (82.5 %,77.7 %) and 0.5 % bile salts (69.3 %, 71.2 %) respectively. They displayed high potassium cyanide tolerance (Pediococcus sp. OG08, 45.7 % and Pichia sp. OG4, 44.7 %). Pediococcus pentosaceus OG08 and Pichia exigua OG4 resulted in the lowest residual cyanide content of 2.75 and 2.80 mg/kg respectively. The unfermented cassava flour had a residual cyanide content of 19.78 mg/kg. Pediococcus pentosaceus OG08 and Pichia exigua OG4 passed safety assessments, were valuable as probiotics due to their beneficial attributes. Cassava effluent possess valuable resource for potential probiotics.